THE IMPACT OF DIVIDEND POLICY, FINANCIAL DISTRESS RISK AND CORPORATE GOVERNANCE TOWARD STOCK PRICE - Ivan Wiyogo; Frinan Satria (ADI Publisher, 2021)
Stock investment is emerging in this era. The market on stock investment will be predicted to grow every year. Stock price is defined by offer and bid price. With this term use in Indonesia Stock Exchange, it makes people hard to guess on what will be the opening price tomorrow as asking price and bidding price need to reach an agreement. This research will investigate the impact of Dividend Policy, Financial Distress Risk, and Corporate Governance as the independent variables toward Stock Price. This research is conducted by using quantitative research method using secondary data that were taken from the LQ45 companies which are listed in Indonesian Stock Exchange with the population of 61 companies. The samples are obtained using purposive sampling method. The total sample is 42 companies from the year 2017-2019. The data analysis is using multiple linear regression analysis. Based on the results of research and analysis by using SPSS 25 indicate that: Dividend per share (dividend policy) and corporate governance have significant impact toward stock price while dividend payout ratio (dividend policy) and distress risk does not have significant impact toward stock price. It is concluded that the impact of dividend policy, financial distress risk and corporate governance is only 29.2% as the rest is impacted by other variables.